Analisis Activated Clotting Time pada Intervensi Koroner Perkutan Elektif dengan Heparin Bolus dan Kontinu di RSUD Dr. Saiful Anwar Malang - Suprapta, Aloysius; Widito, Sasmojo (Jurnal Klinik dan Riset Kesehatan, 2025)
BACKGROUND: Unfractionated heparin effectively prevents thrombosis during percutaneous coronary intervention (IKP). Analysis between sex, age, BMI, diabetes, smoking, CHF, hypertension, stroke, lesion characteristics, CHA2DS2-VASc score, platelet, eGFR, and bleeding events with activated clotting time (ACT) achievement aims to elucidate the correlation in elective IKP procedures using heparin bolus administration followed by continuous heparin. OBJECTIVE: To evaluate the relationship of sex, age, BMI, diabetes, smoking, CHF, hypertension, stroke, lesion characteristics, CHA2DS2-VASc score, platelet, eGFR, and bleeding events on achieving an ACT of ≥300 seconds in elective IKP patients at RSSA. METHODS: This observational study analysed medical records of elective IKP patients at RSSA from July 2022 to August 2024. Data were collected via consecutive sampling. Univariate analysis described sample characteristics, while bivariate analysis assessed variable relationships. Logistic regression was used to develop a predictive model if significant variables was found. RESULTS: Among 43 samples, 34.8% achieved ACT ≥300 seconds. No significant relationship was found among sex, age, BMI, diabetes, smoking, CHF, hypertension, stroke, lesion characteristics, CHA2DS2-VASc score, platelet, and eGFR (p=0.078; p=0.936; p=0.264; p=0.139; p=0.063; p=0.535; p=0.64; p=0.324; p=0.349: p=0.885; p=0.677; p=0.15 respectively). There is no bleeding event after procedure. CONCLUSION: There is no relationship between variables sex, age, BMI, diabetes, smoking, CHF, hypertension, stroke, lesion characteristics, CHA2DS2-VASc score, platelet, and eGFR to ACT achievement in elective IKP patients receiving bolus and continuous heparin. Further research with larger sample sizes and standardized ACT measurements is recommended.